The Influence of Corporate Social Responsibility and Company Values on the Welfare of People's Lives - Suhendar Janamarta; rina aprilyanti; Lia Dama Yanti; Jenni Jenni (Komunitas Dosen Indonesia, 2021)
This study aims to determine: (1) the effect of corporate social responsibility on the welfare of people's lives. (2) The influence of corporate values on the welfare of the community. (3) The influence of corporate social responsibility and company value on the welfare of the community. The sample of this research is based on social responsibility in the Property sector in 2018-2020 using the purposive sampling method. There are 17 companies in 2018-2020 that meet the criteria as research samples. The method of analysis in this study is multiple regression analysis. The results of this study indicate that the disclosure of corporate social responsibility has a positive effect on the welfare of people's lives. The value of the company does not have a positive effect on the welfare of people's lives